PEMAKAIAN KATA REFORMASI DALAM MEDIA MASSA JAWA POS - Wahyudi, Agus Budi; Sabardila, Atiqa (Kajian Linguistik dan Sastra, 2006)
The purpose of the research is to describe the appearance of the word âreformâ, its position in a phrase, other word categories likely to combine, its meaning, and its growth of usage. The method of analysis used is comparison with the technique of referensial, pragmatic, and identification. The result shows that first, constituent cat- egories of reform word are three: word, phrase, and clause. Second, constituent cat- egory of reform word consisted of the word fundamental (reform), verb. (reform), and noun (reformism). Third, the phrase categories of the reform word consisted of the NP, VP, and Preposition P. Fourth, the clause categories consisted of the reform constituent as fillers of S function, P function, C function, O function, topic function, and as clause structure.Â Key words: reform, constituent, category, dan teknik baca markah.